Direct Interaction of Avian Cryptochrome 4 with a Cone Specific G-Protein - Katharina Görtemaker; Chad Yee; Rabea Bartölke; Heide Behrmann; Jan-Oliver Voß; Jessica Schmidt; Jingjing Xu; Vita Solovyeva; Bo Leberecht; Elmar Behrmann; Henrik Mouritsen; Karl-Wilhelm Koch (Cells, 2022)
Background: Night-migratory birds sense the Earth’s magnetic field by an unknown molecular mechanism. Theoretical and experimental evidence support the hypothesis that the light-induced formation of a radical-pair in European robin cryptochrome 4a (ErCry4a) is the primary signaling step in the retina of the bird. In the present work, we investigated a possible route of cryptochrome signaling involving the α-subunit of the cone-secific heterotrimeric G protein from European robin. Methods: Protein–protein interaction studies include surface plasmon resonance, pulldown affinity binding and Förster resonance energy transfer. Results: Surface plasmon resonance studies showed direct interaction, revealing high to moderate affinity for binding of non-myristoylated and myristoylated G protein to ErCry4a, respectively. Pulldown affinity experiments confirmed this complex formation in solution. We validated these in vitro data by monitoring the interaction between ErCry4a and G protein in a transiently transfected neuroretinal cell line using Förster resonance energy transfer. Conclusions: Our results suggest that ErCry4a and the G protein also interact in living cells and might constitute the first biochemical signaling step in radical-pair-based magnetoreception.